Factors Influencing the Risk of Major Amputation in Patients with Diabetic Foot Ulcers Treated by Autologous Cell Therapy - Husakova, J; Bem, R; Fejfarova, V; Jirkovska, A; Woskova, V; Jarosikova, R; Lovasova, V; Jude, E B; Dubsky, M (Journal of diabetes research, 2022)
Introduction: Autologous cell therapy (ACT) is one of the last options for limb salvage in patients with chronic limb-threatening ischemia (CLTI) and diabetic foot ulcers (DFU). However, some patients may still undergo a major amputation even after ACT, but the risk factors for this are not known. Therefore, the aim of our study was to assess the risk factors for major amputation in patients with CLTI and DFU during a 2-year follow-up after ACT. Methods: One hundred and thirteen patients after ACT were included in our study and divided into two groups: Group 1 with major amputation (AMP; n = 37) and Group 2 without amputation (nAMP, n = 76). The risk factors for major amputation were evaluated before ACT and included factors relating to the patient, the DFU, and the cell product. Results: The AMP group had significantly higher C-reactive protein (CRP) levels compared to the nAMP group (22.7 vs. 10.7 mg/L, p = 0.024). In stepwise logistic regression, independent predictors for major amputation were mutation of the gene for methylenetetrahydrofolate reductase (MTHFR) with heterozygote and homozygote polymorphism 1298 (OR 4.33 [95% CI 1.05-17.6]), smoking (OR 3.83 [95% CI 1.18-12.5]), and CRP > 10 mg/L (OR 2.76 [95% CI 0.93-8.21]). Lower transcutaneous oxygen pressure (TcPO2) values were observed in AMP patients compared to the nAMP group at one month (24.5 vs. 33.2, p = 0.012) and at 3 months (31.1 vs. 40.9, p = 0.009) after ACT. Conclusion: Our study showed that the risk for major amputation after ACT in patients with CLTI and DFU is increased by the presence of MTHFR heterozygote and homozygote gene mutations, smoking, and higher CRP at baseline. Lower TcPO2 at one and 3 months after ACT may also have a predictive value. Therefore, it is necessary to stop smoking before ACT, treat any infection, and, above all, consider antiaggregation or anticoagulant treatment after the procedure.
Keywords: Limb Salvage; Chronic Limb-Threatening Ischemia; diabetická noha; amputace; výsledek terapie; Wound Healing; diabetes mellitus; Amputation, Surgical; lidé; adenosinmonofosfát; chronická kritická ischemie končetin; Treatment Outcome; Cell- and Tissue-Based Therapy; záchrana končetiny; Risk Factors; retrospektivní studie; hojení ran; rizikové faktory; Diabetic Foot; buněčná a tkáňová terapie; Diabetes Mellitus; Ischemia; ischemie; Retrospective Studies; Adenosine Monophosphate; Humans